When, where and how to perform efficiency estimation - Oleg Badunenko; Daniel J. Henderson; Subal C. Kumbhakar (Institute for the Study of Labor (IZA), 2011)
In this paper we compare two flexible estimators of technical efficiency in a cross-sectional setting: the nonparametric kernel SFA estimator of Fan, Li and Weersink (1996) to the nonparametric bias corrected DEA estimator of Kneip, Simar and Wilson (2008). We assess the finite sample performance of each estimator via Monte Carlo simulations and empirical examples. We find that the reliability of efficiency scores critically hinges upon the ratio of the variation in efficiency to the variation in noise. These results should be a valuable resource to both academic researchers and practitioners.
urn:nbn:de:101:1-201110263355
Keywords: C14; 330; bootstrap; nonparametric kernel; technical efficiency; Technische Effizienz; Schätztheorie; Data-Envelopment-Analyse; Bootstrap-Verfahren; Monte-Carlo-Methode; Schätzung; USA